Concerns of Parental Substance Abuse and Mental Health Problems Reported to Child Welfare Services—Testing a Moderated Mediation Model for Paths From Reports to Substantiated Concern and Service Provision - Vis, Svein Arild; Lauritzen, Camilla; Havnen, Karen J. S.; Reedtz, Charlotte; Handegård, Bjørn Helge (Frontiers in Psychiatry, 2022)
Background: Parental mental health and substance abuse problems are found in reports of concern to child protection and welfare services. The aim of this study was first to investigate what characterized these reports and how they differed from reports with other types of concerns. Two hypotheses were tested. The first hypothesis was (i) if a report contains concerns about mental health and substance abuse problems, the likelihood of service provision was mediated by substantiation status. The second hypothesis was (ii) that the threshold for substantiation of such problems differed depending on child age, single parent status, and the presence of other child and parent related problems. Method: The study was designed as a case file study which was carried out retrospectively (N=883). A conceptual model was tested in two steps. First a mediation model with direct and indirect paths from reports of concerns through substantiation decision to service provision was tested. Then a second model was expanded to also include moderators for the indirect effects of reported concerns on substantiation decisions. Results: A total of 33.1% of reports about substance abuse and 41.7% of reports about parental mental illness concerns were provided services. The first hypothesis was confirmed. There is a negative direct effect and a positive mediated effect of reported concern on service provision. The second hypothesis was not confirmed. We failed to identify any significant moderating effect of child age, single caregiver status or number of child problems, upon the threshold for substantiation of mental health and drug abuse problems. Conclusions: The total effect of reports about mental illness and substance abuse upon service provision was low. Service provision in cases with suspected substance abuse and/or mental illness is highly dependent upon substantiation of that specific problem. Substantiation threshold is not impacted by other case characteristics. This is surprising because there are good theoretical reasons to assume that parental drug abuse and or mental illness are potentially more detrimental to child health, development and safety if the child is younger, if the parent is a single caregiver, and there are many other parallel concerns.